Preparation of trimers and tetramers of mixed sequence oligodeoxynucleoside methylphosphonates and assignment of configurations at the chiral phosphorus. - Vyazovkina, E V (1993)
Synthesis of stereoregular DNA methylphosphonates has been accomplished for homo-oligomers, but remains a formidable problem for oligomers of a defined antisense target sequence. In this work, four trimer and tetramer deoxynucleoside methylphosphonates of mixed sequence (dACA, dCCAA, dAGGG, and dGCAT) were prepared by block coupling of diastereomerically pure dimers with either monomers or other diastereomerically pure dimers. These oligomers were separated chromatographically into individual diastereomers, and the configurations of the chiral methylphosphonate linkages were assigned. Three types of methods were used to assign configuration of a new methylphosphonate linkage: preparation of the same diastereomer through multiple synthetic pathways, base hydrolysis, and acid hydrolysis. Hydrolysis of the diastereomerically pure oligomers into component dimers and monomers was followed by chromatographic comparison with control dimers of known configuration. In all cases studied, oligomers with R configurations displayed faster elution from silica gel than did oligomers with the respective S configuration. NMR spectra of individual diastereomers of dACA were studied, revealing characteristic differences in chemical shifts which may prove useful in configurational assignments of longer oligomers. Thus, these data provide a methodological basis for synthesis and configurational assignment of longer methylphosphonate oligomers to use as antisense probes.